Elements of museum mobile augmented reality for engaging hearing impaired visitors - Baker, Esraa Jaffar; Abu Bakar, Juliana Aida; Zulkifli, Abdul Nasir (2017)
Nowadays, designers are more concern with the issue of engagement and informal learning at museum and gallery sites.This has made studies to focus more on the use of Mobile Augmented Reality (MAR) at museum and gallery sites. However, most of the MAR applications for museum visitors are largely tailored to normal hearing visitors while the hearing-impaired (HI) visitors are not supported.The hearing impaired (HI) community account for over 5% of the world's populace which is about 360 million people.Thus, this paper explores the design elements of mobile augmented reality for engaging hearing impaired visitors at the museum site.The findings of this paper argues that there are eleven major elements of engagement of MAR needed for the design of an efficient museum MAR app for hearing impaired visitors. These eleven elements include Aesthetics, Curiosity, Usability, Interaction, Motivation, Satisfaction, Self-Efficacy, Perceived Control, Enjoyment, Focused Attention and Interest. This study pointed out that for an efficient and engaged MAR app for the HI community especially HI visitors to museum sites, these eleven elements are critical.This finding will help MAR designers and developers on how to design an efficient and engaged MAR app for the HI community at large and museum HI visitors specifically. © 2017 Author(s).